UJI KINERJA DAN PENGUJIAN LAPANGAN MESIN GRADING TOMAT (Lycopersicum esculentum) TEP-5 - Wahyu K Sugandi; Sudaryanto -; Totok Herwanto (The University of Lampung, 2016)
Laboratory of Agricultural Equipment and Machinery, Department of Industrial Engineering and ManagementAgricultural has designed a tomato grading machine TEP-5 to accelerate post-harvest handling of tomatoes. TheMachine design need to be evaluated to determine it’s performance and quality of tomato grading results. Theresearch method is descriptive analysis. Based on test results, tomato grading machine TEP-5 had an actualcapacity of 4246 Tomato with the engine efficiency of 60,48% and. Engine noise no with and without load was68,3dB and 69,8 dB respectively. Engine vibration generated during no-load test was 2.09 m/s 2 and 2.02 m/s 2with load test. Engine power with and without load respectively 265,8 and 254,8 watt. Tomato quality results frommachine was grading significantly diferrent as compared with the one graded manually. The level of tomatodemage result from grading machine storage at room temperature and cool temperature (<10 o )respectively6.42% and 5.61%. These values were lower as compared to the manual grading. The bruised area of tomatogradeded mechanicaly was 30,19% than that of tomato graded manually. Tomato color was the range of yellowand no difference was observed between manual and mechanical grading.Keyword: grading machine, test performance, self life.